Earnings management, underpricing and post-issue stock performance of SME IPOs in the PRC - Gao, Jing (Curtin University, 2014)
The primary objective of this thesis was to investigate the relationship between earnings management, underpricing, and the post-issue stock performance of PRC SMEs. The analysis was based on a sample of 464 PRC IPOs listed during 2006 to 2010. The higher pre-IPO total discretionary accruals were found to be associated with higher underpricing and poorer post-issue stock performance. The results have important contributions, with implications for various parties, such as investors and authorities.